Mechanosensitivity of macrophage polarization: comparing small molecule leukadherin-1 to substrate stiffness - Joshi, Hemant; Anaya, Edgar; Addanki, Anvitha; Almgren-Bell, Alison; Todd, Elizabeth M.; Morley, Sharon Celeste (Frontiers in Immunology, 2025)
Macrophages sustain tissue homeostasis through host defense and wound repair. To promote host defense, macrophages upregulate surface markers associated with antigen processing and secrete pro-inflammatory mediators such as IL-6 and IL-1β. After pathogen clearance, macrophages shift phenotype to promote wound repair. Shifts in phenotypes are termed “polarization” and have historically been modeled by exposure to soluble mediators such as LPS+IFNγ (host defense) or IL-4+IL-13 (tissue repair). Greater emphasis is now being placed on understanding how the mechanical environment of macrophages, such as tissue compliance, regulates macrophages responses. Here, we compare incubation of primary macrophages on collagen-coated silica gels of varying stiffness to treatment with the small molecule integrin activator, leukadherin-1 (LA1), to examine how substrate stiffness alters macrophage polarization in response to multiple stimuli. LA1 was developed as an immunomodulator to treat inflammatory diseases by impairing trafficking of inflammatory cells. A recent clinical trial examining LA1 as an immunomodulator in solid tumors was terminated early because no benefit was observed. We hypothesized that LA1 treatment may exert additional, unexpected effects on macrophage polarization by replicating mechanotransduction. Specifically, we hypothesized that LA1 would mimic effects of incubation on stiffer substrates, as both conditions would be predicted to activate integrins. Our results show that soft substrate (0.2 kPa) trends towards upregulation of host defense molecules, in contrast to prior reports using different experimental systems. We further show that soft substrates enhance NLRP3-mediated IL-1β production, compared to stiff, in both primary mouse and human macrophages. LA1 mimicked incubation on stiff substrates in inhibiting NLRP3 activation and in regulating expression of several surface markers but differed by reducing IL-6 production. Our results show that macrophage inflammatory responses are regulated by adhesion-based, integrin-mediated mechanical signaling. Modulation of NLRP3-mediated IL-1β production by LA1 supports the possibility of repurposing LA1 to treat NLRP3-dependent inflammatory diseases.